Short-range clinical, dynamic magnetic resonance imaging and P-QOL questionnaire results after mesh repair in female pelvic organ prolapse - Brocker, Kerstin A.; Alt, Celine D.; Corteville, Caroline; Hallscheidt, Peter; Lenz, Florian; Sohn, Christof (European journal of obstetrics & gynecology and reproductive biology, 2011)
Objective - To evaluate clinical, quality-of-life (QoL) and dynamic magnetic resonance imaging (dMRI) results in patients with pelvic organ prolapse (POP) preoperatively, and 4 and 12 weeks after anterior and/or posterior mesh repair. - Study design - Thirty-six patients (mean age 65 years) with symptomatic pelvic floor descent underwent mesh repair. The prolapse was quantified using the POP-Q system. Before surgery as well as 4 and 12 weeks after surgery, the pelvic organ positions were measured on dynamic magnetic resonance imaging during Valsalva manoeuvre in relation to the pubococcygeal and mid-pubic lines to assess surgery outcome. Patients also completed the P-QOL questionnaire to evaluate subjective changes at each visit. - Results - Four and 12 weeks after surgery patients showed improvement of the POP on clinical examination and on dynamic MRI. The latter demonstrated high significance (p<0.001) especially in bladder and vaginal cuff/cervix positions during maximal straining. All quality-of-life domains and some symptom questions of the P-QOL questionnaire significantly improved (p<0.05) 12 weeks after surgery. - Conclusion - Significant anatomical and quality-of-life improvement was demonstrated after anterior and/or posterior mesh repair for POP using dynamic MRI and the P-QOL questionnaire.